Comparative analysis of formulae for umbilical venous catheterization depth based on birth weight - Jingjie Luo; Xu Zheng; Zixin Yang; Keyue Li; Lu Chen; Mingyan Hei (Pediatric Investigation)
ABSTRACT Importance Umbilical venous catheterization (UVC) is a common procedure for critically ill newborn infants. The insertion depth was estimated before the procedure using various formulae. Objective To compare the accuracy of five published formulae based on birth weight (BW). Methods This is a secondary retrospective analysis using data collected in a previous study, in which the actual final insertion depth of UVC was recorded. Predicted insertion depths were calculated by five published formulae based on BW. Then the actual depth and predicted depth were compared. Accurate position was defined as predicted depth being within ± 10% of actual depth. The accuracy rate calculated as “(accurately positioned UVCs/ all UVCs) × 100%” and the ratio of difference calculated as “(|predicted depth − actual depth|/ actual depth)” were compared among five formulae. Results Totally 1298 were enrolled, with gestational age 29.8 ± 2.3 weeks and BW 1215 ± 273 g. The accuracy rates were: Tambasco formula (67.2%), Shukla formula (65.0%), JSS formula (64.4%), BW formula (48.9%), and revised Shukla formula (26.9%). Tambasco formula had the highest accuracy rate in newborns with BW ≥ 1000 g. JSS formula had the highest accuracy rate in newborns with BW<1000 g. Interpretation It is suggested to use the Tambasco formula for estimating the UVC insertion depth for newborns, especially for those with BW ≥ 1000 g, and to apply the JSS formula for newborns with BW < 1000 g. There is no universal formula for achieving 100% accurate positioning.